2011
DOI: 10.1021/la2007809
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Measurements of Interfacial Slip by Colloid Probe Atomic Force Microscopy. I. Mathematical Modeling

Abstract: We developed a stable spread-sheet algorithm for the calculation of the hydrodynamic forces measured by colloid probe atomic force microscopy to be used in investigations of interfacial slip. The algorithm quantifies the effect on the slip hydrodynamic force for factors commonly encountered in experimental measurements such as nanoparticle contamination, nonconstant drag force due to cantilever bending that varies with different cantilevers, flattening of the microsphere, and calibration at large separations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…Our group has recently dedicated significant attention to developing reliable and reproducible measurements and analysis of interfacial slip on rigid surfaces, [30][31][32][33] and here we expand this analysis to soft interfaces, presenting results which match well our molecular dynamic simulations on similar brush systems. 22 2 Experimental section…”
Section: Introductionsupporting
confidence: 62%
“…Our group has recently dedicated significant attention to developing reliable and reproducible measurements and analysis of interfacial slip on rigid surfaces, [30][31][32][33] and here we expand this analysis to soft interfaces, presenting results which match well our molecular dynamic simulations on similar brush systems. 22 2 Experimental section…”
Section: Introductionsupporting
confidence: 62%
“…Thanks to its simplicity, the model (5) finds broad application in the literature 6,10,12,26,[28][29][30][46][47][48] to extract the slip length λ s from experimental data. However, it is mostly employed in the limit k → 0, corresponding to equal slip lengths on both surfaces.…”
Section: Theorymentioning
confidence: 99%
“…Although other expressions for f à have been used in various studies depending on the nature of interacting surfaces, 17,[19][20][21][22][23][24][25] our tests indicated that the physical results remain qualitatively the same as those obtained with Eq. (2).…”
mentioning
confidence: 60%
“…In different experiments for a sphere of radius R ¼ 10 lm the slip lengths in air were found to be b ¼ 23, 48, 80, and 98 nm, while for a larger sphere with R ¼ 50 lm were b ¼ 100 and 120 nm. 17,20,24,25 In any case, the force model for F h z ð Þ is valid for low Reynolds numbers (Re < 1) and short distances so that z ( R. 17,19 Here the mean Reynolds number Rehdz=dtið2RÞ= has values Re $ 0.005-0.07 for R ¼ 10-50 lm where % 15.68 Â 10 À6 m 2 /s is the kinematic viscosity of air and hdz/dti $ (2-3)10 À3 m/s is the mean velocity of the sphere (e.g., see Fig. 2).…”
mentioning
confidence: 99%